The Effect of Service Quality, Price, Customer Satisfaction on Purchase Decisions at Usman Wholesale - Sampurna Tua Hasibuan; Zulkifli Musannip Efendi Siregar; Aziddin Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to examine the effect of service quality, price, and customer satisfaction on purchasing decisions at Wholesale Usman. Quantitative approach with causal associative research method. The research sample was 36 respondents who were determined by accidental sampling technique. The research data was processed using the SPSS version 26.0 application, testing data quality, classical assumption test, correlation coefficient analysis, coefficient of determination, multiple regression, t test and F test. The contribution of service quality variables, price, and customer satisfaction to purchasing decisions is 43, 0% and the remaining 57.0% are contributions from other factors outside the model. The ANOVA test found that the Fcount value of 9.801 was greater than the Ftable value of 2.90 with a 95% confidence level (using a = 5%).